Affective Bias Through the Lens of Signal Detection Theory. Issue 1 (26th April 2021) - Locke, Shannon M.; Robinson, Oliver J.
Affective bias – a propensity to focus on negative information at the expense of positive information – is a core feature of many mental health problems. However, it can be caused by wide range of possible underlying cognitive mechanisms. Here we illustrate this by focusing on one particular behavioural signature of affective bias – increased tendency of anxious/depressed individuals to predict lower rewards – in the context of the Signal Detection Theory (SDT) modelling framework. Specifically, we show how to apply this framework to measure affective bias and compare it to the behaviour of an optimal observer. We also show how to extend the framework to make predictions about bias when the individual holds incorrect assumptions about the decision context. Building on this theoretical foundation, we propose five experiments to test five hypothetical sources of this affective bias: beliefs about prior probabilities, beliefs about performance, subjective value of reward, learning differences, and need for accuracy differences. We argue that greater precision about the mechanisms driving affective bias may eventually enable us to better understand the mechanisms underlying mood and anxiety disorders. Author Summary: We propose applying the Signal Detection Theory framework to understanding the mechanisms behind affective bias in individuals with mood and anxiety disorders. Based on previous explanations of perceptual bias in healthy human observers, we generate five testable hypotheses about the causes of affective bias in clinical populations.